THE INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION AT PT JNE MEDAN BRANCH WITH MOTIVATION AS AN INTERVENING VARIABLE - Rumiris Siahaan; Suci Etri Jayanti; Sri Winda Hardiyanti Damanik; Ayu Zurlaini Damanik; Rakhmawati Purba (Faculty of Law, Universitas Pekalongan, 2023)
The aim of this research was to examine the influence of leadership and work environment on job satisfaction among employees at PT JNE Medan Branch, while also investigating the mediating role of motivation. The study employed a quantitative research design using Smart PLS 3.0 software and explanatory research methodology. The study selected a sample of 57 participants using saturated sampling technique. The results indicated that leadership (X1) had a significant effect on motivation (Z), as did work environment (X2) on motivation (Z). However, leadership (X1) did not have a significant effect on job satisfaction (Y), while work environment (X2) had a significant positive effect on job satisfaction (Y). Furthermore, motivation (Z) had a significant positive effect on job satisfaction (Y). The study also found that motivation did not mediate the relationship between leadership (X1) or work environment (X2) and job satisfaction (Y).